Students' Perception on the use of Guessing Games in Learning English Speaking - Bagus Ali Mahfud*; Elysa Hartati (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This study aims to determine students' perceptions of the use of guessing games in learning to speak English. This study used mixed methods, a combination of qualitative and quantitative methods which were conducted at SMA N 1 Banjar Margo Tulang Bawang. The research sample consisted of twenty one students of eleventh grade in the academic year 2023/2024. Data collection techniques in this study were observation, interviews, and questionnaires. The results showed that students agreed with the use of guessing games in learning to speak English. It has a positive impact on students' speaking skills; they can be more confident and active in learning.